A Single-Cell Immune Topography Identifies CAF-Driven Checkpoint Inhibitor Failure in EGFR-TKI-Resistant Lung Cancer - Shaban, Semaa A.; Hassan, Mohammed Abd; Khalaf, Ban Hamid; Suleiman, Ahmed AbdulJabbar (Asian Pacific Journal of Cancer Biology, 2026)
Background: The heterogeneity of responses to immune checkpoint inhibitors in non-small-cell lung cancer (NSCLC) after failure of EGFR-TKIs (tyrosine kinase inhibitors) is poorly understood as it relates to the tumor microenvironment (TME) and/or cancer-associated fibroblasts (CAFs) contributing to resistance against ABCP therapy. Methods: To investigate these questions, we analyzed seven patients who have failed EGFR-TKI therapy using pretreatment pleural effusions: three who responded, and four who did not. Pre-treatment effusions were processed via single-cell RNA sequencing (GSE233203). Data were processed using Seurat v5 and annotated using scType. Analyses performed included cell proportion modelling, immune module scoring, sub-clustering of CAFs, differential gene expression analysis, and pathway enrichment. Results: A total of 23 cellular clusters were identified from the seven patients. Non-responders exhibited a stromal-dominant and immune-excluded TME featured by high numbers of fibroblasts and mesothelial cells; while responders exhibited an immune-inflamed TME featured by cytotoxic T-cell activity. CAF analysis identified nine distinct CAF sub-types, with nonresponders having the highest abundance of vCAF and ECM+ CAF and GREM1+ CAF populations. Nonresponder CAFs exhibited the upregulation of 1,311 genes, of which a subset was previously characterized as associated with ECM remodeling (extracellular matrix), cytoskeletal organization, and/or neurogenic-like pathways (NRP2, BDNF, and DKK1). Conclusion: Our results suggest that the TME composition prior to initiating ABCP therapy is predictive of response to therapy. Further, our results suggest that programs driven by CAFs, such as stromal programs that promote immune exclusion and resistance, may hinder the efficacy of immunotherapy and therefore targeting the heterogeneity of CAFs may improve patient outcomes.